LITERATURA JUVENIL PREMIADA: DIÁLOGOS ENTRE PESQUISAS ACADÊMICAS, CRÍTICA ESPECIALIZADA, ESCOLA E ADOLESCENTES LEITORES - Souza, Danilo Fernandes Sampaio de (2019)
The dissertation presented here is linked to the investigations of the Research Line Education and Languages of the Graduate Program in Education, and is part of the dialogues of the Research Group Literature and Education , of the Federal University o